Pengaruh Latihan Squats dan Lunges Terhadap Kekuatan Kaki Renang Gaya Dada 50 meter Pada Perenang Pemula Kelompok Umur 10 Tahun dan 12 Tahun di Club Marlin - Valdy Bayu Kelana (Journal of Physical Activity and Sports (JPAS), 2022)
This research was motivated by the concerns of researchers related to the lack of leg strength training in the 50 meter breaststroke swimming, the factors that affect the strength of the breaststroke swimming leg, and it is not known that squats and lunges exercises can increase the strength of the breaststroke swimming leg. The sampling technique in this study uses purposive sampling where the researcher determines the criteria regarding the respondents selected as the sample. Informants in this study were swimmers Club Marlin. The data collection technique in this study used a technique that was test. The analysis was carried out using a quantitative analysis model. The results of research conducted on the effect of squats and lunges on the strength of the legs in the 50-meter breaststroke for beginner swimmers aged 10 years and 12 years at Club Marlin showed that: there was a better effect between before and after being given treatment with squats and lunges exercises on increasing the strength of the legs in the 50-meter breaststroke for beginner swimmers in the 10-year age group and the effect of lunges exercise being more effective for increasing the strength of the 50-meter breaststroke for beginner swimmers in the 10-year & 12-year-old group at Club Marlin.